TOURISM INNOVATION AND ITS ROLE IN ENHANCING THE COMPETITIVE ADVANTAGE OF A TOURISM PRODUCT (World Bulletin of Social Sciences, 2022)
Tourism is one of the most perspective fields in the world economy. This is due to its multifaceted social and economic benefits that helps to solve many global challenges. As a result, many areas have focused on innovation as one of the renewable forms of competition that provides an innovative tourism product and meets the ever-changing needs of tourists. Therefore, the current study aims to explore the role of innovation as a tool to support the competitive advantage of a tourism product. The results of the research show that innovation is a powerful tool that can increase the competitive advantage of a tourism product. This will positively affect on the competitive position of the country. Accordingly, the creation of innovative tourism products and activities will help to popularize the tourism sector and increase its positive impact